DEKONSTRUKSI KONSEP KEPEMIMPINAN KARAENG PATTINGALLOANG DALAM DRAMA KARAENG PATTINGALLOANG KARYA FAHMI SYARIFF - ilham wasi; Mardi Adi Armin; M. Syafri Badaruddin (Universitas Hasanuddin, 2022)
This paper aims to deconstruct the leadership of Karaeng Pattingalloang. as the center of leadership and the roles of subordinates around it. The presence of Karaeng Pattinggaloang has also undergone a process of meaning and has become the value of leadership itself. This research also uses descriptive research and then analyzes it. Data was collected from various sources of literature study. This data is managed to be analyzed to find the meaning of the drama text Karaeng Pattingalloang. The results show that there is a leader-subordinate binary opposition. This hierarchical binary opposition is then disassembled by deconstructing readings so that the angle that is considered to be the bottom position of the first binary shows that the two support each other. Leadership does not stand alone. Instead, subordinates have a central role to support leadership.